A political history of the Arameans: from their origins to the end of their polities - Younger, K. Lawson (Archaeology and Biblical Studies, 2016)
Cover; CONTENTS; PREFACE; FIGURES AND TABLES; ABBREVIATIONS; PRELIMINARY ISSUES; THE ORIGINS OF THE ARAMEANS; THE RISE OF THE ARAMEAN POLITIES IN IRON I; THE ARAMEAN POLITIES OF THE JEZIRAH; BĪT-ADĪNI; SAM'AL/YADIYA/BĪT-GABB